Content Marketing on TikTok and Online Reviews: Impact on Purchase Intentions and Decisions for Gen Z in Indonesia - Wulan, Mutiarasari Nur; Dalimunthe, Nindytia Puspitasari; Husna, Nurul; Nurmalia, Gustika (Economic Education and Entrepreneurship Journal, 2024)
This study try to test the content marketing, online customer reviews, and consumer behavior, namely purchasing decisions and mediated by a preference or purchase interest approach. Local brand bag fashion is a growing trend in society, supported by the major role of social media progress, namely TikTok, especially among generation Z. However, business actors need to understand the characteristics of the TikTok platform and its users well. The existence of interesting marketing content, the creation of online consumer reviews, this can increase consumer interest and ultimately make consumers interested in buying products. The research method used a Google Form questionnaire involving 266 respondents. The purposive sampling is used in this research with the criteria of generation Z who bought local brand bags on the TikTok platform. SMART PLS 4.0 was used to evaluate the data. The study's findings demonstrated that: content marketing significantly and favorably influenced consumer behavior; content marketing significantly and favorably influenced preferences; preferences significantly and favorably influenced consumer behavior; customer reviews significantly and favorably influenced consumer behavior; customer reviews significantly and favorably influenced preferences; content marketing significantly and favorably influenced consumer behavior with preference mediation; and content marketing significantly and favorably influenced consumer behavior with preference mediation.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.215-223